Book Review: Menswear of the Lombards. Reflections in the Light of Archaeology, Iconography and Written Sources - Rena Maguire (EXARC Journal)
Recent archaeological adventures in the beautiful Friulian region of Northern Italy had introduced me to the history of the Langobards, a Germanic people who settled in the Adriatic during the 6th century AD after a long period of southerly migration from the German/Scandinavian Baltic area. Their architecture has stood the test of time, with churches such as the Oratorio di S Maria in Valle (Cividale), and its stunning murals of saints, sinners, kings and clergy. The museum of Cividale del Friuli is replete with their material culture, as they interred grave goods with their dead well into their conversion into Christianity. Yet, there are massive gaps in our knowledge of their everyday life.